Worst of the worst dealing with repressive and rogue nations - Rotberg, Robert I.; World Peace Foundation; ebrary, Inc. (Cambridge, Mass. : World Peace Foundation ; Washington, D.C. : Brookings Institution Press, 2007)
"Identifies and characterizes the most repressive states and singles out which are aggressive. Defines the actions constituting repression and proposes a method of measuring human rights violations, presenting an index of nation-state repressiveness. Offers a way to decide which repressive and rogue states are most deserving of strong policy attention"--Provided by publisher.
Repressive, aggressive, and rogue nation-states : how odious, how dangerous? / Robert I. Rotberg -- Human rights rogues : aggressive, dangerous, or both? / Mary Caprioli and Peter F. Trumbore -- Running the numbers : a comparative perspective / Yi Feng and Saumik Paul -- North Korea : the tyranny of deprivation / Marcus Noland -- Turkmenistan under Niyazov and Berdymukhammedov / Gregory Gleason -- Burma : poster child for entrenched repression / Priscilla A. Clapp -- Winning the African prize for repression : Zimbabwe / Robert I. Rotberg -- Understanding repression in Belarus / Margarita M. Balmaceda -- Equatorial Guinea and Togo : what price repression? / John R. Heilbrunn -- Uzbekistan : a decaying dictatorship withdrawn from the West / Martha Brill Olcott -- Assessing repression in Syria / David W. Lesch -- Tunisia's "sweet little" regime / Clement Henry.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Political persecution; Human rights; Despotism; World politics -- 1989-; Electronic books